Diatom-based reconstruction of Middle to Late Holocene paleoenvironments in Lake Lonkoy, southern Pampas, Argentina - Hassan, Gabriela Susana (2013)
Diatoms recovered from shallow Lake Lonkoy sediment core in southern Pampas, Argentina, were studied in order to assess past environmental conditions. A total of 47 samples were selected from a 1.42-m long core that spans the last 4840 cal. years. Diatoms were extracted by chemical cleaning and studied under light and scanning electron microscopy. A total of 89 diatom taxa were recorded, including 36 taxa that reached>2% relative abundance and were used in statistical analyses. A cluster analysis allowed five significant diatom association zones (DAZ) to be defined. DAZ I (142–92 cm) was dominated by Cyclotella meneghiniana Kützing, Cocconeis placentula Ehrenberg and Nitzschia hustedtiana Salah, and a low abundance of aerophilic taxa, indicating brackish water conditions probably related to the Holocene sea-level high stand. DAZ II (90–48.5 cm) was dominated by C. meneghiniana and Aulacoseira granulata (Ehrenberg) Simonsen, representing a period of high nutrient loading and turbid conditions in the lake, associated with higher water levels and lower salinities than the environmental conditions in DAZ I. The upper 50 cm of the core (DAZ III to V) showed an increase in the dominance of brackish epiphytic and hypereutrophic benthic taxa, indicating an increase in nutrient concentrations associated with agricultural human impacts in the basin. Overall, diatoms allowed major paleoenvironmental changes to be inferred for the lake during the Holocene.